STRENGTHENING THE RULE OF LAW IN IRAQ - Hussein, Daham Smko; Sabir, Hawre Nuraddin (International Journal of Psychosocial Rehabilitation, 2020)
Since the liberation of Iraq, the country has undergone with radical transformations in terms of governance and administration. From 2003 with the change of regime in Iraq, the country has encountered daunting legal and institutional challenges that have pushed Iraq backward, and made the people suffer dramatically. Iraq has historical footprint regarding the rule of law since the Babylonian Dynasty that has the famous ever known Code of Law that dates back to 1772 BC. Which is considered as world’s almost first known codified constitutions. This study lays out a constructive framework for overviewing the rule of law in Iraq, a country which has suffered from the unrest and turmoil in the last 30 years, including interstate and intrastate wars. This study is divided into three main parts, the first session deals with the literature review on rule of law in Iraq. Moreover, the second session deals with the institutions that are linked to the rule of law, and how strengthening the rule of law influences them such as Parliament and Courts. The third part addresses the findings and the policy recommendations for better law enforcement and policy planning in Iraq. The expected results of this study focus on two main priorities as: The Iraqi rule of law is the only tool that affects the Iraqi institutions and this is the only pathway for improved institutional capacity in legal terms. The second is the existing legal system needs to be fully implemented and reviewed over the coming years by taking experience from successful stories around the world. The main thesis questions for this study are; why does the rule of law in Iraq do not work? And what is the state of the rule of law in Iraq after 25 years of Liberation? The methodology is content analysis as the study is descriptive and primary data is not collected, while data from accredited organizations is collected and analyzed accordingly, conclusions and recommendations are drawn from it.